Unusual crystallographic aspects of Microband boundaries within {111}<110> oriented grains in a cold rolled interstitial free steel - Zinnia, N.; Quadir, Md Zakaria; Munroe, P.; Ferry, M. (Iron and Steel Institute of Japan, 2014)
Microbands are well-known deformation features that generate in the rolling microstructures of many metals and alloys. The boundaries across two neighbouring microbands are comprised of dense dislocation walls and they accommodate a small average crystallographic rotation in the range of 1–4°. In this study, a combination of high resolution electron backscattered diffraction (EBSD) and transmission electron microscopy (TEM) was used to observe orientation differences of up to 20° across microband boundaries in the rolling substructures of {111}<110> oriented grains in steel. Despite their high angle nature, the microband interfaces maintain their well-known crystallographic characteristics, by being closely aligned with highly stressed slip planes. Rigid body rotations are argued to take place around the interface normal between adjacent microband lattices. This results in an unusual microstructure whereby alternating microband boundaries, oriented in equal and opposite relative angles, produce an array of orientation pairs in their spatial distributions. © 2014 Iron and Steel Institute of Japan.